ASSESSING THE VIABILITY OF MUZA’RAH AGRO FINANCING AS A SUSTAINABLE SOLUTION FOR SMALL-SCALE FARMERS: A CASE STUDY FROM PAKISTAN - Hamza, Sahibzada Muhammad; Shirazi, Nasim Shah (Bank Indonesia, 2024)
The interplay between the Muza’rah (Sharecropper) agro-financing structure and its impact on rural income and rural poverty alleviation constitutes a multifaceted phenomenon. In this study, we seek to understand of the relation between Muza’rah agro-financing structure and rural income and the mediating role of national agricultural output for the case of Pakistan, a predominantly Muslim country characterized by a well-established Islamic banking and finance infrastructure. Using data from the Pakistan Social and Living Standard Survey (PSLM), the research reveals that the rural per capita income is significantly and negatively related to the Muza’rah agro-financing structure, which is further strengthened by the level of the national agricultural output. The finding underscores the importance of nuanced understanding for policymakers and practitioners engaged in poverty alleviation efforts, emphasizing the need to consider contextual variables and a nation's developmental status when designing interventions to improve rural livelihoods.